3'End labelling of RNA with 32P suitable for rapid gel sequencing. - Winter, G (1978)
A new general method of labelling the 2',3'-diol end of RNA with 32P has been devised suitable for gel sequencing. Poly(A) polymerase (E. coli) is incubated with the RNA and limiting amounts of alpha-32P-ATP. The mono-addition product is then cleaved with periodate and beta-eliminated with aniline, leaving the RNA terminally labelled with 3' 32P-phosphate. When applied to a model compound, tRNAPhe from E. coli, over 28 residues could be read from the 3' end.